Third trimester ultrasound scan combined with a clinical method for accurate birthweight prediction at term: a cohort study in Spain - Rafael Vila-Candel; Francisco Javier Soriano-Vidal; Enrique Castro-Sánchez (Federación Colombiana de Obstetricia y Ginecología, 2019)
Objective: To develop and assess an equation based on maternal clinical parameters and third trimester ultrasound biometry (combined method), and compare it with ultrasound-estimated foetal weight (EFW) calculated using the Hadlock 2 formula. Material and methods: Cohort study. A total of 1,224 women with singleton pregnancies who had undergone foetal ultrasound scanning (USS) at 34 weeks were recruited. The study was conducted at a reference center in Valencia (Spain) between January and December 2016. A gestation-adjusted projection (GAP) method was applied to estimated foetal-weight-for-gestational-age by foetal gender at delivery (EFWa). A multivariate regression was created to estimate foetal weight at term (EFWmr) using anthropometric, demographic, ultrasonographic and obstetric-neonatal variables. EFWa and EFWmr were calculated and compared with actual birthweight. Results: The proportion for EFWmr within <10% of actual birthweight was greater than EFWa (82% vs. 65%, p<0.001). The mean relative error in foetal-weight predictions by using EFWmr was reduced from 6.7% to 0.9% (difference 5.7% 95% CI: 5.4 to 6.0) paired t-test p<0.001, significantly improving the accuracy attainable with USS. The EFWmr outperformed the GAP method in predicting birthweight, within 1% relative error. For newborns <2,500 g, the proportion of estimates within <10% of the actual birthweight for the EFWmr was greater than that of the EFWa (20.4 vs. 16.3%, p=0.005). For babies with normal birthweight (2,500-3,999 g), EFWmr was a better predictor of birthweight than EFWa (84.5 vs. 65.7%, p<0.001). Conclusions: Mathematical modelling to predict birthweight improves third trimester routine ul trasound measurement to estimate neonatal weight at term.